Information Systems and Reverse Logistics: Examining Drivers of Implementation on Multiple Case Study Scenario - Josip Maric; Florence Rodhain; Yves Barlette (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Sustainability is becoming increasingly significant for business researchers and practicioners, where Information Systems (IS) and sustainable development open up a new field of interesting issues to be addressed by scholars. In this paper we present research in progress regarding IS and reverse logistics. Information Systems, in cohesion with closed loop Supply Chain Management (SCM) process, and human resources capability development, produce an innovative service developed to increase efficiency in sustainability efforts and gain increased market value. Our research tends to focus on relationship between IS and closed loop Supply Chains, examining sustainability impact of the reverse logistics and examining organizational competitive advantage gained through sustainability goals. Empirical, rather than theoretical, research and practice regarding this concept is still in its infancy, and with our research we tend to make a contribution to the field. Research model, tools of assessment, in depth description of case studies and preliminary results are presented in the paper as latter.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; management; information systems; sustainability; reverse logistics